ANÁLISE ERGONÔMICA DO TRABALHO EM UMA OFICINA MECÂNICA - Souza, Estéfane Coelho da Silva; Moreira, Guilherme Victor; Santos, Vitoria do Carmo Gomes dos; Resende, Márcia Colamarco Ferreira (Sinapse Múltipla, 2020)